QTL mapping for plant height and ear height using bi-parental immortalized heterozygous populations in maize - Yang, Haoxiang; Zhang, Ziran; Zhang, Ning; Li, Ting; Wang, Junjie; Zhang, Qing; Xue, Jiquan; Zhu, Wanchao; Xu, Shutu (Frontiers in Plant Science, 2024)
Plant height (PH) and ear height (EH) are key plant architectural traits in maize, and they affect the photosynthetic efficiency and high plant density tolerance of maize, as well as its suitability for mechanical harvesting, which can have a major effect on yield. In this study, the genetic effects of quantitative trait loci (QTL) for the PH and EH of maize and their regulatory mechanisms were explored. QTL mapping of PH and EH was performed using a recombinant inbred line (RIL) population and its corresponding immortalized backcross (IB) populations generated from crosses of the RIL population with the two parental lines. A total of 17 and 15 QTL were detected in the RIL and IB populations, respectively. Two QTL, qPH1-1 (qEH1-1) and qPH1-2 (qEH1-4) in the RIL, were simultaneously identified for PH and EH. Genome-wide association and co-expression network analyses revealed five candidate genes with high confidence in the QTL that could be detected in at least two populations/locations; the homologs of Zm00001d011117 and Zm00001d011108 were confirmed to play a role in determining PH in maize and soybean, respectively. These findings provide new insights that could be used to improve the architecture of maize plants.